Effects of plyometric training on physical fitness in prepuberal soccer athletes - Negra, Y.; Chaabene, H.; Sammoud, S.; Bouguezzi, R.; Aymen Abbes, M.; Hachana, Y.; Granacher, U. (International Journal of Sports Medicine, 2017)
This study aimed at examining the effects of plyometric training on stable (SPT) vs. unstable (UPT) surfaces on physical fitness in prepuberal soccer players. Male athletes were randomly assigned to SPT (n=18; age=12.7±0.2 years) or UPT (n=16; age=12.2±0.5 years). Both groups conducted 3 regular soccer training sessions per week combined with either 2 SPT or UPT sessions. Assessment of jumping ability (countermovement jump [CMJ], and standing long jump [SLJ]), speed (10-m, 20-m, 30-m sprint), agility (Illinois agility test [IAT]), and balance (stable [SSBT], unstable [USBT] stork balance test; stable [SYBT], unstable [UYBT] Y balance test) was conducted pre-and post-training. An ANCOVA model was used to test for between-group differences (SPT vs. UPT) at post-test using baseline values as covariates. No significant differences were found for CMJ height (p>0.05, d=0.54), SLJ (p>0.05; d=0.81), 10-m, 20-m, and 30-m sprint performances (p>0.05, d=0.00-0.24), IAT (p>0.05, d=0.48), and dynamic balance (SYBT and UYBT, both p>0.05, d=0.39, 0.08, respectively). Statistically significant between-group differences were detected for the USBT (p<0.01, d=1.86) and the SSBT (p<0.01, d=1.75) in favor of UPT. Following 8 weeks of SPT or UPT in prepuberal athletes, similar performance levels were observed in both groups for measures of jumping ability, speed, dynamic balance, and agility. However, if the goal is to additionally enhance static balance, UPT has an advantage over SPT.